Language Stimulation for Children with Mental Retardation-An Activity Manual for Parents (Global Journal of Human-Social Science, 2013)
The objectives of the Study To develop training activities and guidelines suitable for north Indian home settings in an activity manual and to field test the developed material on a group of Hindi-English speaking parents of mental retardation Method 20 Parents and 20 Special educators Mental Retardation were included in this study Field Study tool Questionnaire was developed on the base of coverage of content use of language style of presentation and difficulties in home implementation Questionnaire and activities described in the manual were given to all the subjects for one week reading and they were asked to rate the questionnaire
Keywords: language stimulation; activity manual; mental retardation; home; parents; children; special educators; questionnaire